"It's Like Tuskegee in Reverse": A Case Study of Ethical Tensions in Institutional Review Board Review of Community-Based Participatory Research - Malone, Ruth E; Yerger, Valerie B; McGruder, Carol; Froelicher, Erika (American journal of public health (1971), 2006)
Community-based participatory research (CBPR) addresses the social justice dimensions of health disparities by engaging marginalized communities, building capacity for action, and encouraging more egalitarian relationships between researchers and communities. CBPR may challenge institutionalized academic practices and the understandings that inform institutional review board deliberations and, indirectly, prioritize particular kinds of research. We present our attempt to study, as part of a CBPR partnership, cigarette sales practices in an inner-city community. We use critical and communitarian perspectives to examine the implications of the refusal of the university institutional review board (in this case, the University of California, San Francisco) to approve the study. CBPR requires expanding ethical discourse beyond the procedural, principle-based approaches common in biomedical research settings. The current ethics culture of academia may sometimes serve to protect institutional power at the expense of community empowerment.